Developing a cortex specialized for face perception. - Cohen Kadosh, K; Johnson, M (2007)
Recent developmental functional magnetic resonance imaging studies provide evidence that the cortical specialization for face perception observed in adults emerges only gradually over the first decade of childhood. These developmental results provide a middle-ground view on the long-standing debate in the literature from adults about the specificity or otherwise of face-sensitive areas of cortex. According to this developmental perspective, certain cortical regions become specialized for face perception in adults, partly as a result of a decade or more of experience and partly as a result of initial biases.